2022
DOI: 10.56294/mw202212
|View full text |Cite
|
Sign up to set email alerts
|

Effective communication and shared decision making: Theoretical approach from the doctor-patient relationship approach

Javier Gonzalez-Argote

Abstract: Introduction: shared decision making is understood as a communicational model in which health personnel collaborate with the patient or caregiver in making optimal health decisions, encouraging patients, family members and physicians to evaluate clinical information and compare risk-benefit in order to select the most appropriate treatment option.Objective: to characterize shared decision making as a model of patient-physician communication.Development: the method has gained acceptance among the medical commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…(5) Usha Tiwari Upadhyay, 2020 reported that after undergoing a positive psychological intervention, children with SLD saw a considerable improvement in their emotional well-being in terms of greater life satisfaction, boosted positive effects, and diminished negative consequences. (8) n accordance with S. Pandiammal and S.J. Poornakala, 2020, total self-esteem scores for the control and experimental groups were low before the intervention, at 14,21 and 14,20, respectively.…”
Section: Intervention Used To Specific Learning Disabilitiessupporting
confidence: 66%
See 3 more Smart Citations
“…(5) Usha Tiwari Upadhyay, 2020 reported that after undergoing a positive psychological intervention, children with SLD saw a considerable improvement in their emotional well-being in terms of greater life satisfaction, boosted positive effects, and diminished negative consequences. (8) n accordance with S. Pandiammal and S.J. Poornakala, 2020, total self-esteem scores for the control and experimental groups were low before the intervention, at 14,21 and 14,20, respectively.…”
Section: Intervention Used To Specific Learning Disabilitiessupporting
confidence: 66%
“…Gila Schnitzer, Caroline Andries, Jo Lebeer 2007 and Usha Tiwari Upadhyay, 2020. (6,8) Similarly, EsmaielSoleymani, MojtabaHabibi and Mani B. Monajemi 2015;Valeria Cavioni, IlariaGrazzani and Veronica Ornaghi 2017; Ahmed Elhassan Hamid Hassan 2015; Karande S 2022; Syed Arifa and Syed ShahidSiraj 2019; Peter A. Wyman et al 2010; Elisabetta Lombardi 2021indicative distinctions between the elements of alexithymia and mental health were discovered.Students with dyscalculia gain psychologically and in terms of their alexithymia component through adopting emotional regulation strategies. (10,11,12,13,14,15,16) Problems with thinking, being unable to stay focused, unwillingness to pay attention, lack of activity, lack of conversations, lack of self-assurance, low self-esteem, hostility, overconsumption of activity, non-interaction, hyper-crime, phobia, and short-duration sleep are some of the emotional and behavioural issues that affect children with learning disabilities.According to research made by SutinunJuntorn, SarinyaSriphetcharawut, Peeraya Munkhetvit,2017 and S. Pandiammal and S.J.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations